FORENSIC-MEDICAL ASPECTS OF ROAD TRAFFIC TRAUMATISM AND DEATHS ANALYZE BY MATERIALS BUREAU FME STATE ADMINISTRATION IN POLTAVA REGION - Mustafina, G.M.; Chernyak, V.V.; Lukachina, Ge.I. (World of Medicine and Biology, 2012)
Following road accident in Poltava region directly related to sweeping development infrastructure and motor transport increase, amount of settlement territory, situated near the highway Kiev-Kharkov.
Keywords: forensic-medical expertise; consequences of accidents; Poltava region; highway Kiev-Kharkov; EVRO-2012